Biomimetic Assembly of Leucoridine A1. Issue 9 (17th February 2015) - Benayad, Sarah; Beniddir, Mehdi A.; Evanno, Laurent; Poupon, Erwan
Abstract: The three‐step biomimetic assembly of leucoridine A, a pseudosymmetric bisindole of Leuconotis griffithi (Apocynaceae) is described. The semisynthetic route provides suitable conditions toward the central 3‐spiro‐1, 2, 3, 4‐tetrahydropiperidine ring connecting the two subunits of the highly congested structure. The biomimetic assembly by a Diels–Alder or alternatively an imino‐Rauhut–Currier reaction affords the natural ( S )‐diastereomer of leucoridine A as the sole product. The sequence, repeated in a one‐pot cascade, supports a non‐enzymatic pathway for the assembly of this bisindole and the known related alkaloids. Abstract : The biomimetic cascade assembly of leucoridine A, a pseudosymmetric bisindole of Leuconotis griffithi (Apocynaceae) is described. The semisynthetic route provides suitable conditions toward the central 3‐spiro‐1, 2, 3, 4‐tetrahydropiperidine ring connecting the two subunits of the highly congested structure. The biomimetic assembly by an imino‐Rauhut–Currier reaction affords the natural ( S )‐diastereomer of leucoridine A as the sole product.